Nutritional value of baled rice straw for ruminant feed - Peripolli, Vanessa (2016)
The objectives of this study were to evaluate the effects of cultivation and hay making factors on chemical composition, protein fractionation, and digestibility in rice straw, as well as to identify the chemical fractions that contribute to the variation in its nutritional value for ruminants. Statistical procedures were performed in a model that included rice crop cycle, sowing season, baling season, soil classification, fertilizer application, and productivity (kg/ha) as fixed effects and the hay bale as random effect. Chemical composition, protein fractionation, and digestibility data were subjected to multivariate analyses including factor, cluster, and discriminant. Considering the cultivation and haymaking factors, development cycle, baling season, and grain production explained the most variation in the rice straw nutritional value. Straws derived from early maturing cultivars showed the lowest levels of neutral detergent fiber, acid detergent fiber, acid detergent insoluble nitrogen, and C nitrogen fraction in comparison with straw originating from mid cycle cultivars. Rice straw from more productive cultivars had lower levels of lignin and C fraction as well as higher levels of crude protein and B3 fraction compared with straws from less productive cultivars. However, the main variation in the nutritional value between the samples of rice straw was related to the baling season. The bailing seasons were grouped in two clusters. Straws with better nutritional value were those with lower levels of cell wall fractions, from more productive crops, with early development cycle and baled until March. Rice crop cycle, baling season, and grain production effects explain the variation in the nutritional value of rice straws. Straws with better nutritional value have lower levels of fractions related to secondary cell wall and lignification.